Distribution of pediatric intensive care beds in Brazil: Regional inequalities and implications for equity in the public health system - Luís Felipe Ribeiro Soares; Maria Auxiliadora Souza Mendes Gomes; Saint Clair Gomes Júnior (PLoS ONE, 2025)
Background Pediatric Intensive Care Units (PICUs) play a critical role in reducing child mortality, but their distribution across Brazil remains markedly uneven. Understanding how the spatial and technological distribution of PICU beds relates to regional child health indicators is essential for promoting equity within the Unified Health System (SUS). Objective To examine the national distribution of PICU beds in Brazil, identify regional inequality patterns, and explore their association with pediatric mortality to inform equitable health planning. Methods This cross-sectional ecological study analyzed data from the National Register of Health Establishments (CNES) and demographic indicators from the Brazilian Institute of Geography and Statistics (IBGE) , encompassing all 5,570 municipalities and 450 health regions as of July 2023. Variables included the number and type of PICU beds (types I, II, and III), resident population, proportion of individuals under 14 years, and mortality in this age group. A multivariate cluster analysis was applied to group health regions by similarities in bed availability and mortality profiles, using Bayesian and Akaike Information Criteria and the Silhouette coefficient to define cluster quality. Results A total of 6,489 PICU beds were identified in 708 healthcare providers, with 50% allocated to SUS. Most beds were type II (64.7%), followed by type III (18.6%) and type I (16.6%). Six clusters were identified, revealing marked inequalities: regions with higher proportions of type III beds had lower child mortality (16.5 per 100,000), while areas with predominantly type I beds or none had higher mortality (up to 25.0 per 100,000). Notably, 259 health regions (46%) lacked any PICU beds, affecting over 53 million residents. Conclusions The unequal distribution of PICU beds across Brazil reflects structural inequities in access to pediatric critical care. Policies should prioritize regionalized, quality-based allocation, intergovernmental coordination, and integration of health data systems to guide equitable expansion of pediatric intensive care capacity within the SUS.